Satellite Cell Mitotic Activity of Broilers Fed Differing Levels of Lysine - Pophal, Simone; Mozdziak, Paul E.; Vieira, Sergio L. (International Journal of Poultry Science, 2004)
Post-hatch myofiber growth is dependent upon the addition of new nuclei from the mitotically active satellite cell population. The objective of this study was to examine the relationship between different levels of dietary lysine and satellite cell mitotic activity during the early post-hatch period. Broiler chicks were split into five groups of 10 birds each immediately post-hatch. One group was not provided any feed or water for the first three days post-hatch, whereas the other groups were provided a standard starter diet with different levels of lysine (0.82, 0.99, 1.16, 1.33%) for the first three days post-hatch. All birds were injected with 5-Bromo-2`-deoxyuridine (BrdU) 2 hours before they were killed on the third day post-hatch. Mitotically active satellite cells were identified in the Pectoralis thoracicus and quantified using BrdU immunohistochemistry in combination with computer-based image analysis. Satellite cell mitotic activity was significantly (P < 0.05) lower in the starved compared to any of the fed groups. However, satellite cell mitotic activity was highest (P < 0.05) in the birds that were provided a lysine deficient diet (0.82%). The current study suggests that it is possible to nutritionally stimulate the satellite cell population in the early post-hatch chick, and that it is an important endeavour to re-examine the nutritional requirements of the early post-hatch chick to optimize meat yield.